An atypical pleomorphic lipomatous tumor arising on the cheek. (2nd August 2019) - Boyd, Alan S.
Abstract: Pathologists and dermatopathologists commonly encounter tumors with adipocyte differentiation. Most are of minimal clinical significance. Those exhibiting atypical spindle cell morphology have been reported but the terminology for such neoplasms is unsettled. Tumors with both spindle cell and pleomorphic morphology are rare, with equally unsettled descriptive nomenclature. Recently, a series of such tumors, termed atypical pleomorphic lipomatous tumor, has been published. They resided in the deep soft tissue or subcutis. To date, such a tumor has not been reported with dermal involvement.